Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Karyawan - Fairly Maulana Andhito Putra; Cahyo Adhi Nugroho; Akbar Dwiansyah; Indah Rizki Maulia (Global Leadership Organizational Research in Management, 2024)
Review Article: Leadership and Work Environment Impact Employee Performance. A scientific article that generates research hypotheses on variable interactions for Performance Management research. This Literature Review article used Google Scholar, Mendeley, and other academic online platforms for literature research. This Literature Review concludes: 1) Leadership; 2) Work environment; 3) Leadership's impact on employee performance. These two exogenous variables affect motivation and performance, along with many others like organizational culture, job satisfaction, and workload. Many other factors, such as effective leadership and work environment, affect motivation and performance in addition to the two exogenous variables